2017
DOI: 10.1038/s41598-017-03700-1
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of cGVHD by C5a/C5aR blockade is associated with increased frequency of Treg

Abstract: C5aR signaling plays an important role in the regulation of T cell activation and alloimmune responses in chronic graft-versus-host disease (cGVHD). However, direct evidence of this modulation and the efficacy of C5aR blockade in the treatment of cGVHD have not been demonstrated. We observed higher expression of C5aR on both monocytes and T cells of patients with cGVHD compared with healthy controls and non-GVHD patients after allogeneic hematopoietic stem cell transplantation. Our data also demonstrated a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The mouse cGVHD model was established as previously described [ 24 ]. Briefly, 10- to 12-week-old BALB/cJ H-2d female mice (Beijing Vital River Laboratory Animal Technology Co., Ltd., China) as recipients received irradiation followed by a tail vein injection of 8 × 10 6 bone marrow cells and 8 × 10 6 spleen cells from B10.D2 male mice, the donors purchased from Jackson Laboratories, Bar Harbor, USA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse cGVHD model was established as previously described [ 24 ]. Briefly, 10- to 12-week-old BALB/cJ H-2d female mice (Beijing Vital River Laboratory Animal Technology Co., Ltd., China) as recipients received irradiation followed by a tail vein injection of 8 × 10 6 bone marrow cells and 8 × 10 6 spleen cells from B10.D2 male mice, the donors purchased from Jackson Laboratories, Bar Harbor, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Blank control mice received equal amounts of a PBS injection. The disease score and skin score were determined as previously described [ 24 ], and survival was checked daily for 60 days. The criteria of skin score were briefly determined as follows: healthy appearance = 0, skin lesions with alopecia less than 1 cm 2 in area = 1, skin lesions with alopecia 1 to 2 cm 2 in area = 2, and skin lesions with alopecia more than 2 cm 2 in area = 3.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, blocking and deficiency of both C5a and C5aR have been associated with improved allograft survival ( 39 , 40 ). In addition, expression of and signaling through both C3aR and C5aR on nTregs has been reported to inhibit Treg function ( 3 , 41 ), while pharmacological blockade of C5a has been associated with increased frequency of Tregs in a mouse GvHD model and with increased microvascular and epithelial repair in murine airway allografts ( 7 , 24 , 42 ). These findings prompted us to investigate a possible relationship between the complement cascade and T regulatory cells, which when combined may further amplify the regulatory mechanism of tissue recipients.…”
Section: Introductionmentioning
confidence: 99%
“…16,21,54,101 In addition, expression of C3aR and C5aR on nTregs has been associated with suppression of Treg-cell functions, 11,18 and recent subsequent studies demonstrated that C5a blockade favors an increase of systemic Tregs, which are vital to microvascular and epithelial repair in the murine airway allografts. 15,17,172 These findings further highlighted the existence of C5a-C5aR T cell signaling, which rebalances Tregs and T effs population during inflammation, and this novel C5a C5aR-axis during acute rejection episodes may be an effective therapeutic strategy in combination with other immunosuppressive regimens for preventing the development of chronic rejection. 16 In a recent study in mouse airway transplantation, it was found that C5a blockade induces an increase in CD4 + FOXP3 + Tregs systemically followed by an upregulation of IL-5, TGF-, IL-10, and reduction of IFN-and IL-6 mRNA gene expression, which favors a state of immunotolerance.…”
Section: Complement and Costimulatory Signalsmentioning
confidence: 77%
“…This molecular signaling suggested that complement deficiency or blockade can potentially attenuate T cell‐mediated autoimmunity (Treg and T‐effector cell balance) and, therefore, blocking and deficiency of both C5a and C5aR have been associated with improved allograft survival . In addition, expression of C3aR and C5aR on nTregs has been associated with suppression of Treg‐ cell functions, and recent subsequent studies demonstrated that C5a blockade favors an increase of systemic Tregs, which are vital to microvascular and epithelial repair in the murine airway allografts . These findings further highlighted the existence of C5a‐C5aR T cell signaling, which rebalances Tregs and T effs population during inflammation, and this novel C5a C5aR‐axis during acute rejection episodes may be an effective therapeutic strategy in combination with other immunosuppressive regimens for preventing the development of chronic rejection .…”
Section: Complement Factor and T‐regulatory Cell Interactionsmentioning
confidence: 90%